Co-infection of Echinococcus equinus and Echinococcus canadensis (G6/7) in a gray wolf in Turkey: First report and genetic variability of the isolates - Kilinc, Seyma Gunyakti; Celik, Figen; Kesik, Harun Kaya; Selcuk, Muhammed Ahmed; Ahmed, Haroon; Simsek, Sami (Elsevier, 2023)
Cystic echinococcosis (CE) is an important zoonotic diseases caused by larval form of Echinococcus granulosus sensu lato. The material of this study was the gray wolf (Canis lupus), which was found dead in the rural area of Bingol province of Turkey. The animal was brought to Veterinary Faculty for necropsy and many of adult Echinococcus spp. obtained. A total of 9 whole adult worms were morphologically examined under the micro-scope, gDNA was isolated from individual samples, a partial mt-CO1 gene fragment (875 bp) was amplified with PCR and sequenced. According to the phylogenetic analysis, six worms were characterized as E. equinus, while three were reported as E. canadensis (G6/7). It was found that the haplotypes of both species were similar to previously published haplotypes. This is the first report in which E. equinus and E. canadensis (G6/7) adult parasites were detected together in a gray wolf's intestine. The findings are important in that it draws attention to the importance of wild cycle in the spread of CE.
Keywords: Echinococcus equinus; E. canadensis (G6/7); Gray wolf; Haplotype; Turkey